Aquadag for demolding tungsten-molybdenum alloy forgings and preparation method of aquadag
By using graphite milk composed of colloidal graphite powder and other components, the problem of easy oxidation and decomposition of traditional graphite milk at high temperature forging of tungsten-molybdenum alloy is solved, and chemical stability and lubricating performance at high temperatures of 1700-2000℃ is achieved, which reduces mold losses and improves product quality.
Patent Information
- Application Number
- CN202510399925.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the forging of tungsten-molybdenum alloy, traditional graphite milk is prone to oxidation and decomposition at high temperatures, resulting in reduced lubricity and adhesion, causing product and mold adhesion to stick, difficult to demold, and serious mold loss.
Graphite milk composed of colloidal graphite powder, silicon carbide, dispersant, binder, thickener, defoaming agent and sodium carbonate solution is used to disperse evenly through ball milling processes to ensure stable pH and chemical stability at high temperatures of 1700-2000℃.
The graphite milk maintains excellent lubricating performance and adhesion at high temperatures, prevents product and mold adhesion, reduces mold loss, and improves the production efficiency and product quality of forgings.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tungsten-molybdenum alloy forging, in particular to a graphite emulsion for demoulding tungsten-molybdenum alloy forgings and a preparation method thereof. Background Art
[0002] Tungsten-molybdenum alloys are widely used in aerospace, military, electronics and other fields due to their unique physical and chemical properties. Since the forging temperature of tungsten-molybdenum alloys is usually between 1700-2000℃, graphite emulsion is needed for lubrication in order to demold during the forging process of tungsten-molybdenum alloys. However, due to the high melting point and high hardness of the alloy, demolding becomes a technical problem. Traditional graphite emulsions have problems with unstable pH values and easy oxidation and decomposition at high temperatures (especially 1700-2000℃), which leads to reduced lubricity and adhesion, resulting in adhesion between the product and the mold, difficulty in demolding, and serious mold loss. Therefore, the development of a graphite emulsion that can maintain chemical stability and lubrication properties at high temperatures is of great significance to improving the production efficiency and product quality of tungsten-molybdenum alloy forgings. Summary of the invention
[0003] The purpose of the present invention is to provide a high-temperature stable graphite emulsion for demolding of tungsten-molybdenum alloy forgings, which can maintain a stable pH value and chemical stability at a high temperature of 1700-2000°C, is not easily oxidized and decomposed, thereby maintaining excellent lubrication and adhesion, effectively preventing adhesion between the product and the mold, and reducing mold loss.
[0004] To achieve the above object, the present invention provides the following technical solutions: A graphite emulsion for demoulding tungsten-molybdenum alloy forgings, characterized in that it is composed of the following components in percentage by mass: 15%-30% of colloidal graphite powder, 5%-8% of dispersant, 0.8%-1.2% of silicon carbide, 8%-12% of binder, 10%-20% of thickener, 1%-2% of defoamer, 4%-5% of sodium carbonate solution, and the balance is water.
[0005] Furthermore, the colloidal graphite powder has a particle size of less than 2 μm and a purity of 99%.
[0006] Furthermore, the binder is sodium silicate.
[0007] Furthermore, the thickener is a mixture of sodium starch phosphate and polyoxyethylene.
[0008] Furthermore, the dispersant is prepared by mixing polyethylene glycol and acetylene glycol polyether in any proportion.
[0009] Furthermore, the concentration of the sodium carbonate solution is 15%.
[0010] A method for preparing a graphite emulsion for demoulding a tungsten-molybdenum alloy forging comprises the following steps: adding colloidal graphite powder into water and stirring evenly, then sequentially adding a dispersant, silicon carbide, a binder, a thickener, a defoamer, and a sodium carbonate solution, stirring sufficiently to obtain a mixture A, and then ball milling the mixture A to obtain a uniformly dispersed graphite emulsion.
[0011] Furthermore, after adding the colloidal graphite powder into water, the water is placed in a wet mixer for stirring for 10-20 minutes.
[0012] Furthermore, the component raw materials in the formula are fully stirred and mixed together to obtain a mixture A, and the stirring and mixing time is 2-5 hours.
[0013] Further, the obtained mixture A is placed in a high-energy ball mill, the rotation speed of the ball milling jar of the high-energy ball mill is 400 r / min-500 r / min, and the ball milling time is 20-25 h.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. High temperature stability and excellent lubrication performance: Colloidal graphite powder is used to replace flake graphite powder, and an appropriate amount of silicon carbide and a high temperature resistant pH stabilizer sodium carbonate solution are added to the system, so that it can maintain stable chemical properties and pH value at high temperatures of 1700-2000°C, and is not easy to oxidize and decompose. At the same time, the nano-scale structure of colloidal graphite powder can form a denser lubrication film, reducing the direct contact between the mold and the workpiece and reducing the wear rate.
[0015] 2. On the one hand, the present invention utilizes a combination of a dispersant and a thickener, that is, a mixture of polyethylene glycol and acetylene glycol polyether is used as a dispersant, which can effectively disperse the colloidal graphite particles and prevent agglomeration, and utilizes sodium starch phosphate and polyoxyethylene for synergistic thickening to form a three-dimensional network structure, thereby improving the adhesion and shear resistance of the graphite emulsion. This combination optimizes the rheological properties, ensures that the graphite emulsion is evenly coated under high temperature and high pressure, and also has an anti-rust effect; on the other hand, a binder and a defoamer are introduced, that is, sodium silicate is used to form a stable silicate glass layer at high temperature, thereby enhancing the bonding force between the graphite emulsion and the mold, and the polyether-modified silicone type and the defoamer have both high temperature resistance and long-term defoaming ability, thereby avoiding the decomposition and failure of traditional defoamers at high temperatures.
[0016] 3. The colloidal graphite powder used in the present invention has a smaller particle size (<2μm) and a higher purity (99%), which reduces the contamination of forgings by impurities and improves the qualified rate of finished products; in addition, non-toxic sodium carbonate is used instead of ammonia water to avoid the release of harmful gases in the production process, which meets the requirements of green manufacturing.
[0017] In summary, the present invention replaces key ingredients (colloidal graphite powder, sodium carbonate solution) and coordinates the optimization of various ingredients (dispersant, thickener, binder, etc.), so that the prepared graphite emulsion is particle-free and non-corrosive, and the oxidation resistance, self-lubrication, chemical stability and environmental protection of the graphite emulsion in a high-temperature forging environment are significantly improved, and the core defects of the prior art (difficult demolding at high temperature and high mold loss) are solved, and it can well meet the forging production of rare metal alloys such as tungsten and molybdenum at high temperatures of 1700-2000°C. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0019] A graphite emulsion for demoulding tungsten-molybdenum alloy forgings is composed of the following components in percentage by mass: 15% of colloidal graphite powder with a particle size of less than 2 μm and a purity of 99%, 0.8% of silicon carbide, 5% of a dispersant, the dispersant being a mixture of polyethylene glycol and acetylene glycol polyether in a mass ratio of 1.5:1, 8% of a binder, i.e. sodium silicate, 10% of a thickener, which is a mixture of sodium starch phosphate and polyoxyethylene, wherein the sodium starch phosphate and the polyoxyethylene are 5% each, 1% of a defoamer, i.e. a polyether-modified organic silicon type defoamer, 4% of a stabilizer, i.e. a sodium carbonate solution with a concentration of 15%, and the balance being water.
[0020] The preparation method is as follows: after adding the above-mentioned colloidal graphite powder into water, placing it in a wet mixer and stirring evenly to obtain a suspension, the stirring time is 10 minutes; then adding a dispersant, silicon carbide, a binder, a thickener, a defoaming agent, and a sodium carbonate solution in sequence, mixing evenly, the mixing time is 2 hours, and a mixture A is obtained; then the mixture A is placed in a high-energy ball mill for ball milling to refine the viscous mixture, and further mixing evenly to obtain a uniformly dispersed graphite emulsion, wherein the rotation speed of the ball mill is 400 r / min, the ball milling time is 25 hours, and the weight of the grinding balls is 0.4 kg. Example 2
[0021] A graphite emulsion for demoulding tungsten-molybdenum alloy forgings is composed of the following components in percentage by mass: 25% of colloidal graphite powder with a particle size of less than 2 μm and a purity of 99%, 8% of a dispersant, the dispersant being a mixture of polyethylene glycol and acetylene glycol polyether in a mass ratio of 1:1.5, 12% of a binder, i.e. sodium silicate, 16% of a thickener, which is a mixture of sodium starch phosphate and polyoxyethylene, wherein the sodium starch phosphate and the polyoxyethylene are 8% each, 2% of a defoamer, i.e. a polyether-modified silicone defoamer, 1.2% of silicon carbide, 5% of a stabilizer, i.e. a sodium carbonate solution with a concentration of 15%, and the balance being water.
[0022] The preparation method of the above-mentioned graphite emulsion is as follows: after adding the above-mentioned colloidal graphite powder into water, placing it in a wet mixer and stirring it evenly to obtain a suspension, and the stirring time is 20 minutes; then adding a dispersant, silicon carbide, a binder, a thickener, a defoaming agent, and a sodium carbonate solution in sequence, mixing them evenly, and mixing them for 5 hours to obtain a mixture A; then placing the mixture A in a high-energy ball mill for ball milling to refine the viscous mixture, and further mixing it evenly to obtain a uniformly dispersed graphite emulsion, wherein the rotation speed of the ball mill is 500r / min, the ball milling time is 20 hours, and the weight of the grinding balls is 0.8kg. Example 3
[0023] A graphite emulsion for demoulding tungsten-molybdenum alloy forgings is composed of the following components in percentage by mass: 30% of colloidal graphite powder with a particle size of less than 2 μm and a purity of 99%, 5% of a dispersant, the dispersant being a mixture of polyethylene glycol and acetylene glycol polyether in a mass ratio of 1:0.8, 8% of a binder, i.e. sodium silicate, 20% of a thickener, which is a mixture of sodium starch phosphate and polyoxyethylene, wherein the sodium starch phosphate and the polyoxyethylene are 10% each, 2% of a defoamer, i.e. a polyether-modified organic silicon type defoamer, 1% of silicon carbide, 5% of a stabilizer, i.e. a sodium carbonate solution with a concentration of 15%, and the balance being water.
[0024] The preparation method of the above-mentioned graphite emulsion is as follows: after adding the above-mentioned colloidal graphite powder into water, placing it in a wet mixer and stirring it evenly to obtain a suspension, and the stirring time is 20 minutes; then adding a dispersant, silicon carbide, a binder, a thickener, a defoaming agent, and a sodium carbonate solution in sequence, mixing them evenly, and mixing them for 5 hours to obtain a mixture A; then placing the mixture A in a high-energy ball mill for ball milling to refine the viscous mixture, and further mixing it evenly to obtain a uniformly dispersed graphite emulsion, wherein the rotation speed of the ball mill is 500r / min, the ball milling time is 24h, and the weight of the grinding balls is 0.8kg. Example 4
[0025] A graphite emulsion for demoulding tungsten-molybdenum alloy forgings is composed of the following components in percentage by mass: 20% of colloidal graphite powder with a particle size of less than 2 μm and a purity of 99%, 6% of a dispersant, the dispersant being a mixture of polyethylene glycol and acetylene glycol polyether in a mass ratio of 2:1, 10% of a binder, i.e. sodium silicate, 20% of a thickener, which is a mixture of sodium starch phosphate and polyoxyethylene, wherein the sodium starch phosphate and the polyoxyethylene are 10% each, 1% of a defoamer, i.e. a polyether-modified silicone defoamer, 1% of silicon carbide, 4% of a stabilizer, i.e. a sodium carbonate solution with a concentration of 15%, and the balance being water.
[0026] The preparation method of the above-mentioned graphite emulsion is as follows: after adding the above-mentioned colloidal graphite powder into water, placing it in a wet mixer and stirring it evenly to obtain a suspension, and the stirring time is 15 minutes; then adding a dispersant, silicon carbide, a binder, a thickener, a defoaming agent, and a sodium carbonate solution in sequence, mixing them evenly, and mixing them for 3 hours to obtain a mixture A; then placing the mixture A in a high-energy ball mill for ball milling to refine the viscous mixture, and further mixing it evenly to obtain a uniformly dispersed graphite emulsion, wherein the rotation speed of the ball mill is 400r / min, the ball milling time is 24h, and the weight of the grinding balls is 0.4kg. Example 5
[0027] A graphite emulsion for demoulding tungsten-molybdenum alloy forgings is composed of the following components in percentage by mass: 25% of colloidal graphite powder with a particle size of less than 2 μm and a purity of 99%, 5% of a dispersant, the dispersant being a mixture of polyethylene glycol and acetylene glycol polyether in a mass ratio of 1:2, 10% of a binder, i.e. sodium silicate, 20% of a thickener, which is a mixture of sodium starch phosphate and polyoxyethylene, wherein the sodium starch phosphate and the polyoxyethylene are 10% each, 2% of a defoamer, i.e. a polyether-modified silicone defoamer, 0.8%-1.2% of silicon carbide, 5% of a stabilizer, i.e. a sodium carbonate solution with a concentration of 15%, and the balance being water.
[0028] The preparation method of the above-mentioned graphite emulsion is as follows: after adding the above-mentioned colloidal graphite powder into water, placing it in a wet mixer and stirring it evenly to obtain a suspension, and the stirring time is 15 minutes; then adding a dispersant, silicon carbide, a binder, a thickener, a defoaming agent, and a sodium carbonate solution in sequence, mixing them evenly, and mixing them for 5 hours to obtain a mixture A; then placing the mixture A in a high-energy ball mill for ball milling to refine the viscous mixture, and further mixing it evenly to obtain a uniformly dispersed graphite emulsion, wherein the rotation speed of the ball mill is 500r / min, the ball milling time is 25h, and the weight of the grinding balls is 0.8kg. Example 6
[0029] A graphite emulsion for demoulding tungsten-molybdenum alloy forgings is composed of the following components in percentage by mass: 25% of colloidal graphite powder with a particle size of less than 2 μm and a purity of 99%, 5% of a dispersant, i.e. a mixture of polyethylene glycol and acetylene glycol polyether in equal mass ratios, 10% of a binder, i.e. sodium silicate, 20% of a thickener, which is a mixture of sodium starch phosphate and polyoxyethylene, wherein the sodium starch phosphate and the polyoxyethylene are 10% each, 2% of a defoamer, i.e. a polyether-modified organic silicon-type defoamer, 1% of silicon carbide, 5% of a stabilizer, i.e. a sodium carbonate solution with a concentration of 15%, and the balance being water.
[0030] The preparation method of the above-mentioned graphite emulsion is as follows: after adding the above-mentioned colloidal graphite powder into water, placing it in a wet mixer and stirring it evenly to obtain a suspension, and the stirring time is 18 minutes; then adding a dispersant, silicon carbide, a binder, a thickener, a defoaming agent, and a sodium carbonate solution in sequence, mixing them evenly, and mixing them for 4 hours to obtain a mixture A; then placing the mixture A in a high-energy ball mill for ball milling to refine the viscous mixture, and further mixing it evenly to obtain a uniformly dispersed graphite emulsion, wherein the rotation speed of the ball mill is 500r / min, the ball milling time is 25h, and the weight of the grinding balls is 0.8kg.
[0031] Comparative Example 1 A graphite emulsion is composed of the following ingredients in percentage by mass: 20% of flake graphite powder, 5% of polyethylene glycol, a binder, namely 10% of sodium borate, a thickener, namely 20% of hydroxypropyl methylcellulose, a defoamer, namely 2% of polyether-modified silicone defoamer, a stabilizer, namely 5% of ammonia solution with a concentration of 25%, and the balance being water.
[0032] The preparation method comprises the following steps: adding the flake graphite powder to water, placing the flake graphite powder in a wet mixer and stirring the mixture evenly to obtain a suspension, wherein the stirring time is 20 minutes; then adding the dispersant, thickener, binder, defoamer and stabilizer, mixing the mixture evenly for 5 hours to obtain a mixture, and then placing the mixture in a high-energy ball mill for ball milling to refine the viscous mixture, further mixing the mixture evenly to obtain a uniformly dispersed graphite emulsion, wherein the rotation speed of the ball mill is 500 r / min, the ball milling time is 25 hours, and the weight of the grinding balls is 0.8 kg.
[0033] In order to prove the effect of the high temperature stable graphite emulsion for demoulding of tungsten-molybdenum alloy forgings of the present invention, we conducted the following tests and recorded the relevant data. The following are the details of the test and the analysis of the results: 1. Purpose of the test
[0034] The chemical stability, lubricity and adhesion of the graphite emulsion of the present invention at high temperature and its influence on die loss and forging quality were evaluated.
[0035] 2. Experimental Materials and Methods
[0036] 1. Test materials: The high temperature stable graphite emulsion of the present invention (samples prepared in Example 1 and Example 6), traditional graphite emulsion (comparative sample prepared in Comparative Example 1), tungsten-molybdenum alloy forging die, and tungsten-molybdenum alloy material.
[0037] 2. Test methods: 2.1 The demoulding effect, die loss, forging quality and oxidation resistance were compared and tested. The test results are shown in Table 1.
[0038] 2.1.1 The graphite emulsions prepared in Examples 1 and 6 of the present invention and the conventional graphite emulsion prepared in Comparative Example 1 were coated on the same mold surface respectively, and forging was performed after drying.
[0039] The forging temperature was set to 1800°C, the pressure to 20 MPa, and the forging speed to 5.2 m / s.
[0040] Record the demoulding effect, die loss and forging surface quality during the forging process.
[0041] 2.1.2 The graphite emulsions prepared in Examples 1 and 6 of the present invention and the conventional graphite emulsion prepared in Comparative Example 1 were coated on the same mold surface respectively, placed in a room at room temperature and dry, and the time when rust appeared on the mold surface was recorded.
[0042] The experimental results are shown in Table 1
[0043] Table 1
[0044] 2.2 High temperature performance test: The graphite emulsions prepared in Examples 1-6 and the conventional graphite emulsion prepared in Comparative Example 1 were heated at 1800° C. for 2 hours, respectively, and then their chemical stability, pH value and lubrication performance were tested. The results are shown in Table 2.
[0045] Table 2
[0046] Through the above test data and result analysis, it can be concluded that the high temperature stable graphite emulsion for demoulding of tungsten-molybdenum alloy forgings of the present invention has excellent chemical stability and lubrication performance at high temperature, can effectively prevent the adhesion between the product and the mold, reduce mold loss, and improve the surface quality of the forging. Compared with traditional graphite emulsions, the graphite emulsion of the present invention has better application effect in forging processing.
[0047] It can be seen from the above table that compared with traditional graphite emulsions, the graphite emulsion of the present invention has excellent oxidation resistance, self-lubrication and chemical stability at high temperatures (1700-2000°C), thereby being able to well meet the forging production of rare metal alloys such as tungsten and molybdenum at high temperatures of 1700-2000°C.
[0048] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0049] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.
Claims
1. A graphite emulsion for demoulding tungsten-molybdenum alloy forgings, characterized in that: It is composed of the following ingredients in percentage by mass: colloidal graphite powder 15%-30%, dispersant 5%-8%, silicon carbide 0.8%-1.2%, binder 8%-12%, thickener 10%-20%, defoamer 1%-2%, sodium carbonate solution 4%-5%, and the balance is water.
2. The graphite emulsion for demoulding tungsten-molybdenum alloy forgings according to claim 1, characterized in that: The colloidal graphite powder has a particle size of less than 2 μm and a purity of 99%.
3. The graphite emulsion for demoulding tungsten-molybdenum alloy forgings according to claim 1, characterized in that: The binder is sodium silicate.
4. The graphite emulsion for demoulding tungsten-molybdenum alloy forgings according to claim 1, characterized in that: The thickener is prepared by mixing sodium starch phosphate and polyoxyethylene.
5. The graphite emulsion for demoulding tungsten-molybdenum alloy forgings according to claim 1, characterized in that: The dispersant is prepared by mixing polyethylene glycol and acetylene glycol polyether in any proportion.
6. The graphite emulsion for demoulding tungsten-molybdenum alloy forgings according to claim 1, characterized in that: The concentration of the sodium carbonate solution is 15%.
7. The method for preparing the graphite emulsion according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Add colloidal graphite powder into water according to the formula ratio and stir evenly to obtain a suspension; (2) adding the dispersant, silicon carbide, binder, thickener, defoamer and sodium carbonate solution to the suspension obtained in step (1) in order according to the formula ratio, stirring while adding, and obtaining a mixture A after sufficient stirring; (3) The mixture A obtained in step (2) is placed in a high-energy ball mill, and is fully ball-milled and further mixed to obtain a uniformly dispersed graphite emulsion.
8. The method for preparing graphite emulsion according to claim 7, characterized in that: When the colloidal graphite powder described in step (1) is added into water and stirred, the stirring time is 10-20 minutes.
9. The method for preparing graphite emulsion according to claim 7, characterized in that: The time for fully stirring and mixing the components and raw materials in the formula in step (2) is 2-5 hours.
10. The method for preparing graphite emulsion according to claim 7, characterized in that: In step (3), the ball milling time is 20-25 hours.
Citation Information
Patent Citations
Water based release agent for high temperature resistant composite material
CN108060005A
Precision forging release agent and preparation method thereof
CN110591804A
Environment-friendly water-based metal working fluid and preparation method thereof
CN110628498A
Release agent made from polyoxyethylene ether-20 oleoyl ricinoleate
CN111136771A
Pre-dispersed particle, plastic master batch and preparation method thereof
CN113372712A
Cited By
Aquadag prepared from spherical graphite tailings and preparation method of aquadag
CN121672516A